2006
DOI: 10.1086/511154
|View full text |Cite
|
Sign up to set email alerts
|

A Semiempirical Magnetohydrodynamical Model of the Solar Wind

Abstract: We present a new MHD model for simulating the large-scale structure of the solar corona and solar wind under "steady state" conditions stemming from the Wang-Sheeley-Arge empirical model. The processes of turbulent heating in the solar wind are parameterized using a phenomenological, thermodynamical model with a varied polytropic index. We employ the Bernoulli integral to bridge the asymptotic solar wind speed with the assumed distribution of the polytropic index on the solar surface. We successfully reproduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
224
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(227 citation statements)
references
References 26 publications
2
224
0
1
Order By: Relevance
“…The physics of this domain is described by the equations of MHD, with additional source terms required to take into account the heating and acceleration of the solar wind (Groth et al 2000;Usmanov et al 2000). Recently, Cohen et al (2007) developed a solar wind model based on the empirical relationship between solar wind speed and magnetic flux tube expansion (Wang & Sheeley 1990), which has been incorporated into the SWMF. Here we use the coronal model presented in Roussev et al (2003b).…”
Section: Numerical Methods: Swmf and Bats-r-usmentioning
confidence: 99%
“…The physics of this domain is described by the equations of MHD, with additional source terms required to take into account the heating and acceleration of the solar wind (Groth et al 2000;Usmanov et al 2000). Recently, Cohen et al (2007) developed a solar wind model based on the empirical relationship between solar wind speed and magnetic flux tube expansion (Wang & Sheeley 1990), which has been incorporated into the SWMF. Here we use the coronal model presented in Roussev et al (2003b).…”
Section: Numerical Methods: Swmf and Bats-r-usmentioning
confidence: 99%
“…The most up to date models are fully three dimensional and self-consistent (Vidotto et al 2009(Vidotto et al , 2012 and use more physically motivated arguments to determine mass loss rates (Holzwarth & Jardine 2007;Cohen et al 2007;Cranmer & Saar 2011). However many assumptions are used and scaling relations are still present in some models.…”
Section: Stellar Wind Modelsmentioning
confidence: 99%
“…This code has previously been used to model both the solar corona (Groth et al 2000;Roussev et al 2003b;Cohen et al 2007;van der Holst et al 2010) and CMEs (e.g., Groth et al 2000;Manchester et al 2004;Roussev et al 2003a;Tóth et al 2007;van der Holst et al 2009), and has recently been greatly advanced for the purpose of simulating highenergy, high-density laser experiments . The MHD system of equations given below comprises the coronal model (as given in van der and is solved with the BATS-R-US code:…”
Section: System Of Equationsmentioning
confidence: 99%
“…CMEs have typically been simulated with single-fluid three-dimensional (3D) magnetohydrodynamical (MHD) models that address only the thermodynamics of the ion species, and assume that the electrons must be of the same temperature. The thermodynamics of the corona for these models have been addressed with empirical heating functions (Groth et al 2000) or a variable adiabatic index (Wu et al 1999;Roussev et al 2003b;Cohen et al 2007). An examination of the temperature structure resulting from a CME-driven shock simulated with the coronal model of Groth et al (2000) is found in Manchester et al (2004).…”
Section: Introductionmentioning
confidence: 99%